Double Spinned Lobster (Panulirus penicillatus) fishery in Wonogiri Regency, Central Java Province: sustainable management strategies - Yusli Wardiatno; Beni Beni; Akhmad Solihin; Zairion Zairion (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2020)
The purpose of this research was to analyze the issues and problems in lobster fisheries for establishing strategies to achieve sustainable lobster management. This study was conducted from November 2018 to January 2019 in coastal waters of Wonogiri Regency, Central Java Province. Data collection were made using the triangulation method. In addition, data analyses were performed using AWOT (Analythical Hierarchy Procedure and Strenght-Weakness-Opportunity-Threats) which was the combination of SWOT and Analytical Hierarchy Process (AHP) techniques. The results showed that the problems of lobster management in Wonogiri Regency was the unreported catch and the unwillingness to release small-size- and berried-female lobsters. The best strategy for lobster management in Wonogiri Regency was shown in the 2nd quadrant (strategi Strength-Threats). Thus, the priority strategies would be the development of friendly lobster fishing gear with score a value 35.4% and the second priority is strengthening the role of collectors in controlling catches with a value of 30.5%.